IS THE ANNUAL LEAVE AN AD INFINITUM RIGHT? - Bogdan IONIȚĂ (Challenges of the Knowledge Society)
In 2015, the Romanian Labor Code was amended in order to transpose a vast and constant CJEU case law in this field, providing that in the event the employee, for justified reasons, cannot take the annual leave during the year in which it was accrued, the employer is under the obligation to grant the employee the untaken leave days, with his consent, in a reference period of 18 months, calculated from the start of the year following the one in which the right to annual leave was accrued. In the same context, the Labor Code expressly provided for the accrual of annual leave in certain cases where workers cannot perform work due to objective reasons, such as, but not limited to medical leave and maternity leave. The above cited regulation gave rise to endless debates in the legal literature regarding aspects such as (i) whether the right to annual leave lapses upon expiry of the 18 months term and, (ii) whether in such a case the corresponding right to payment of an allowance in lieu of leave not taken upon expiry of the 18 months also lapses. This study intends to address the above-mentioned questions and suggests an approach that takes into account both the purpose (ratio legis) of the annual leave and the legal nature thereof, as well as the recent CJEU case law rendered in the interpretation of Directive 2003/88, pursuant to which the workers’ right to annual leave may be construed as lapsed in cases where (i) the employer is able to prove that it enabled workers to exercise their right to paid annual leave in a concrete and transparent manner and (ii) the worker refused to benefit from annual leave voluntarily.